2014
DOI: 10.1159/000356792
|View full text |Cite
|
Sign up to set email alerts
|

Association between Endotoxin Activity and Acute Kidney Injury in Cardiac Patients Undergoing Cardiopulmonary Bypass

Abstract: Background/Aims: Cardiopulmonary bypass (CPB) has been thought to promote endotoxin translocation from the gut. Increased endotoxin activity (EA) has been related to a worsening of organ dysfunction, particularly acute kidney injury (AKI). This study aims to determine if CPB could influence EA after cardiac surgery, and if EA variations are associated with renal dysfunction following CPB. Methods: This was an observational study of patients subjected to complex cardiac surgery, likely to last for >120 min. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Systemic hypotension, direct renal vasoconstriction, activation of vasoactive hormones, and activation of inflammatory pathways by endotoxins might all contribute to sepsis-associated AKI [ 21 ]. The release of endotoxin into the circulatory system is a well-documented phenomenon that occurs during cardiopulmonary bypass procedure and after its discontinuation [ 9 ], which likely originates from increased endothelial permeability following ischemia and reperfusion of the gut. Increased EA has been previously associated with renal dysfunction in the setting of infection and sepsis involving altered glomerular filtration, renal tubular damage, and inflammation, leading to cell apoptosis [ 21 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic hypotension, direct renal vasoconstriction, activation of vasoactive hormones, and activation of inflammatory pathways by endotoxins might all contribute to sepsis-associated AKI [ 21 ]. The release of endotoxin into the circulatory system is a well-documented phenomenon that occurs during cardiopulmonary bypass procedure and after its discontinuation [ 9 ], which likely originates from increased endothelial permeability following ischemia and reperfusion of the gut. Increased EA has been previously associated with renal dysfunction in the setting of infection and sepsis involving altered glomerular filtration, renal tubular damage, and inflammation, leading to cell apoptosis [ 21 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Monti et al [ 8 ] also showed that high EA level in patients with sepsis was associated with higher vasopressor requirements and increased hospital mortality as compared with intermediate and low EA groups. While elevation in EA occurs as a result of gram-negative bacteremia, high EA levels have also been reported to occur independent of gram-negative bacteremia [ 9 , 10 ], suggesting the potential for endotoxin translocation across a dysfunctional gastrointestinal barrier. Furthermore, ischemia-mediated gut barrier dysfunction contributing to organ failure, in the absence of primary gastrointestinal injury, has been supported by experimental models [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that higher EAA levels were associated with AKI in patients with COVID-19 [16, 17]. A small study in 18 patients undergoing cardiopulmonary bypass procedure also demonstrated elevated EAA levels in patients who developed AKI versus those who did not [20]. In the current study, only 9/124 patients (7.3%) were positive for SARS-CoV-2, therefore our study is the first to show correlations between serial endotoxin levels and kidney outcomes in a broad cohort of critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we compared the APACHE II scores, SOFA scores, inotropic scores, lactate, and Cr levels, which are reported factors related to endotoxemia evaluated by EA levels. [4,7,23] NT pro-BNP [24] and procalcitonin, [25] which have been reported to be prognostic biomarkers for sepsis, were also compared. The association between variables was assessed using Wilcoxon rank sum testing and Fisher exact test.…”
Section: Methodsmentioning
confidence: 99%